ROLE OF PYRIDOXINE HYDROCHLORIDE IN THE DEVELOPMENT OF TOLERANCE TO THE TOXIC ACTION OF ISONIAZID IN ANIMALS - K. I. Usov; T. A. Guskova; G. G. Yushkov (Туберкулез и болезни лёгких)
The objective of the study: to assess the impact of continuous and course (intermittent) use of pyridoxine hydrochloride in combination with isoniazid on the rate of tolerance development in rats under conditions of a toxicological experiment.Subjects and methods. Isoniazid (tablets, 0.3 g.) and the substance of pyridoxine hydrochloride (powder, 50.0 g.) were used for the experiment. Male white rats were used as experimental biological models.Main results. The article presents data on experimental study of toxicologic tolerance of rats to the anti-tuberculosis drug of isoniazid with its administration simultaneously with pyridoxine hydrochloride. The obtained data provided the evidence about the impact of pyridoxine hydrochloride on the rate of how fast the host developed the tolerance to the toxic action of isoniazid. It has been proved that intermittent (by short courses) use of pyridoxine hydrochloride with isoniazid versus its continuous use resulted in a slower development of toxicological tolerance to isoniazid in rats.